ATTITUDE TOWARDS KNOWLEDGE SHARING, SUBJECTIVE NORM INCREASE NURSES’ KNOWLEDGE SHARING AND INNOVATIVE WORK BEHAVIOR - Yusran, Resadana; Purwandari, Dian Alfia; Anindita, Rina (Universitas Trisakti, 2022)
This Study aims to explore the influence of Attitude towards Knowledge, Subjective Norm, and High-Performance Work System on Knowledge Sharing and Innovative Work Behavior. The primary data was obtained by using non-probability purposive sampling technique via online questionnaires. Data was analyzed by using Structural Equation Modeling (SEM). The respondent were nurses in RSUP. Dr. M. Djamil Padang. The results of this study showed that Subjective Norm has the strongest effect on Knowledge Sharing, followed by Attitude towards Knowledge Sharing, and High-Performance Work System. High-Performance Work System also has positive and direct impact on Innovative Work Behavior. Knowledge Sharing has the strongest effect on Innovative Work Behavior. The results of this study provide managerial implication for the company to identify physiological factors and HRM practice promoting Knowledge Sharing and Innovative Work Behavior. The proper knowledge management and HRM practice makes the company enable to innovate and to enhance competitive advantages.